Soil compaction and soybean root growth - Rosolem, Ciro Antonio [UNESP]; Takahashi, M. (Springer, 1998)
Soil compaction has a negative effect and Ca was shown to enhance root growth. The effects of soil subsurface compaction and liming on root growth and nutrient uptake by soybean were studied at the Department of Agriculture and Plant Breeding, São Paulo State University, Brazil. A Dark Red Latosol, sandy loam (Haplortox) was limed to raise base saturations to 40.1, 52.4 and 66.7%. The experimental pots were made of PVC tubes with 100 mm of diameter. Three rings with 150, 35 and 150 mm long were fixed one on the top of the other. In the central ring of 35 mm, the soil was compacted to bulk densities of 1.06, 1.25, 1.43 and 1.71 g.cm(-3). There was no effect of base saturation on soybean root and shoot growth and nutrition. Subsurface compaction led to an increase in root growth in the superficial layer of the pots with a correspondent quadratic decrease in the compacted layer. There was no effect of subsoil compaction on total root length and surface, soybean growth and nutrition. Soybean root growth was decreased by 10% and 50% when the soil penetrometer resistances were 0.52 MPa (bulk density of 1.45 g.cm(-1)) and 1.45 MPa (bulk density of 1.69 g.cm(-3)), respectively. In spite of the poor root growth in the compacted layer, once it nas overcome the root system showed an almost complete recovery.
Keywords: Glycine max; macronutrients; root length; soil compaction